IDENTIFIKASI DAN PEMETAAN LAHAN SAWAH DENGAN CITRA SATELIT RESOLUSI TINGGI DAN TRACKING GPS - Nurlina, Nurlina (Lambung Mangkurat University Press, 2011)
The availability of productive land becomes one of the main problems in thedevelopment of food security and independence of Indonesian farmers. After theregional autonomy era begins, the food business is the responsibility of localgovernment, both at provincial and district / city, the implementation and operationalexcellence tailored to the potential for their respective regions. Act No. 7 of 1996 onFood, in particular article 45, 46, 47, and 48 explain that achieve food security is theresponsibility of the government and the community. In order to support making theright decisions to maintain local food security, support is needed more accurate data,especially in raw paddy fields as the main source of producing rice. Extensive datacollection of raw paddy fields along with other supporting data, basically to increasethe availability of extensive data and information materials on various levels ofadministrative fields that have a high accuracy. Satellite imagery interpretation thatcan produce high accuracy is high-resolution satellite imagery such as Ikonos orimage Quickbird image. Based on the results of this mapping is concluded that thetotal land area of raw rice is obtained from measurements in four districts (Kec.Barabai, Kec. Labuan Amas Selatan, Kec. Labuan Amas Utara and Kec. Haruyan) inMiddle River Upper District is 25,277.35 ha consisting of 9,311.17 ha of rainfedlowland, 1,876.00 and 14,090.18 ha irrigated lowland.